Activities Analysis of Encapsulated Mitragyna speciosa Extracts in High-Fat Diet-Induced Rats Model: In vivo and In silico Studies : Nanoparticles of M. speciosa to High-fat Diet Rats - Khoirul Rista Abidin; Mas Rizky AA Syamsunarno; Aziiz Mardanarian Rosdianto; Kelana Kusuma Dharma; Ronny Lesmana; Nasrul Wathoni; Sriwidodo Sriwidodo (Indonesian Journal of Herbal and Biomedical Research, 2025)
Background: UCP-1 deficiency can be addressed through the activation of thermogenesis using various herbs, including Mitragyna speciosa (M. speciosa ). Purpose: This study aims to evaluate the efficacy of M. speciosa extracts, encapsulated in nanoparticles, in stimulating the activity of UCP-1 . Methods: The research utilized an in silico approach to test the docking of Mitragynine and epinephrine ligands against β1 and β3 adrenergic receptors. The nanoparticles were prepared using chitosan, alginate, and polyethylene glycol (PEG). An in vivo study was performed utilizing Wistar rats subjected to a high-fat diet (HFD) and assigned to six groups: Normal, HFD, HFD + MG50, HFD + Npm5, HFD + Npm10, and HFD + Npm20. The induction period for all groups was set at four weeks. Results: The docking tests yielded binding scores of -189.55 for Mitragynine against the β1 adrenergic receptor and -179.76 for the β3 receptor. The interactions between Mitragynine and the adrenergic receptors involved amino residues similar to those found in the native ligand epinephrine, specifically Asn1006A, Ser1007A, and Asn1022A for β1, and Asn332R for β3. Nanoparticles at doses of 5, 10, and 20 mg/kg BW demonstrated significant differences (p < 0.05) in body temperature and UCP-1 levels. Notably, the 10 and 20 mg/kg BW dosages did not lead to weight gain in the rats (p > 0.05). Conclusion: Mitragynine shows potential as an agonist for β1 and β3 adrenergic receptors. Furthermore, the nanoparticles at 5, 10, and 20 mg/kg BW were effective in stimulating UCP-1 activity and elevating body temperature in rats subjected to a high-fat diet.